Analysis and Design of Multistory Building Using Different Structural Systems - Mohamed Rahim, Mohamad Radiham (Universiti Teknologi Petronas, 2006)
Skeleton frame system and load bearing wall system are common structural system being used in high-rise and mid-rise building. These systems may have significant advantages and disadvantages against each other. The decision on using which system may require careful justification in order to build an economical, easy, and fast-toconstruct building beside the stability and the durability of the building. In this study, a layout of a multistory building is to be designed using both systems. Both layout systems are then will be analyzed for the same live load as a control factor. The overall cost for the building is mainly depending on the quantity of materials used in the construction. Comparing the quantity of materials used to build the building, the load bearingwall system uses about 60% more concreteand steel reinforcement bars than the frame system. The load bearing wall system also found to require only minimum wall thickness with minimum reinforcement bars in the design. By reversing the calculation to determine the reinforcement for the walls, it is found that the minimum wall thickness with minimum reinforcement can stand the load of 1473.5 kN/ m length of wall while the maximum loads on the wall is only 577.36 kN/m length of wall (about 50% of the capacity). It is concluded that the frame system is suitable for any height and any floor arrangement while the load bearing wall system is more suitable for building with height morethan 30 storey with similarfloor layout in everyfloor..